2002
DOI: 10.1246/cl.2002.204
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Nitrate Ions on Tin-Modified Platinum and Palladium Electrodes

Abstract: The tin-modified platinum and palladium-deposited gold (Sn/Pt and Sn/Pd/Au) electrodes have exhibited a higher electrocatalytic activity for the reduction of nitrate than any electrode so far reported in the literature. Ammonium ions were predominantly formed on Sn/Pt, while N2O and/or N2 were the most likely main products on Sn/Pd/Au.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 12 publications
3
61
0
Order By: Relevance
“…Electrocatalytic reduction of nitrate process is extremely complex, and the products are highly sensitive to the electrode material used (Shimazu et al, 2001;Peel et al, 2003). In this paper, we show that the Pd:Sn molar ratio on the ACF is an important factor for catalytic activity and selectivity.…”
Section: Effect Of the Pd:sn Molar Ratio On The Nitrate Reductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Electrocatalytic reduction of nitrate process is extremely complex, and the products are highly sensitive to the electrode material used (Shimazu et al, 2001;Peel et al, 2003). In this paper, we show that the Pd:Sn molar ratio on the ACF is an important factor for catalytic activity and selectivity.…”
Section: Effect Of the Pd:sn Molar Ratio On The Nitrate Reductionmentioning
confidence: 77%
“…Vooys et al (2000) found that Cu-modified Pd electrode showed higher activity for nitrate reduction than a single metal. Whereafter, Shimazu et al (2001) reported that the Sn-modified platinum and Pd electrodes revealed the highest electrocatalytic activity. However, the use of expensive bulk platinum and Pd is a disadvantage for practical purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vooys et al [19] found that Cu-modified Pd electrodes showed higher activity for nitrate reduction than single metal electrodes. Shimazu et al [22] reported that Sn-modified Pt and Pd-Au electrodes exhibited the highest electrocatalytic activity. However, the non-affordability of these electrodes limits their application at an industrial scale and few studies were conducted to investigate the performance of Pd-Sn in the electro-catalytic reduction for nitrate removal.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of electrode substrates have been investigated and include silver [51], cadmium [52], platinum [53], gold [54] and, more recently, boron-doped diamond [55,56]. Various alloys and catalytic deposits have also been investigated, typically involving nickel [57], copper [58 -60], tin/palladium [61,62] and platinum/rhodium [63].…”
Section: New Developmentsmentioning
confidence: 99%